2022
DOI: 10.21037/tp-21-519
|View full text |Cite
|
Sign up to set email alerts
|

Long-term neurological outcomes of children with neuroblastoma with opsoclonus-myoclonus syndrome

Abstract: Background: Neuroblastoma with opsoclonus-myoclonus syndrome (OMS-NB) is a rare disease in children. Few studies of long-term outcome of children with OMS-NB were conducted. This study aimed to review the rate of recovery of neurological symptoms and the long-term neurological outcomes of children with OMS-NB. Methods: This study retrospectively assessed 14 children with OMS-NB diagnosed at Peking University First Hospital from May 2011 to November 2019. Demographic data, neurological symptoms, oncological sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Speech and behavioral problems are especially detected. [19][20][21][22] The rate of neurological sequelae, including the persistence of OMAS symptoms, was reported as 56.5% in one study, while in another, it was reported between 20 and 60%. 13,22 In our study, the rate of sequelae is 33%.…”
Section: Discussionmentioning
confidence: 90%
“…Speech and behavioral problems are especially detected. [19][20][21][22] The rate of neurological sequelae, including the persistence of OMAS symptoms, was reported as 56.5% in one study, while in another, it was reported between 20 and 60%. 13,22 In our study, the rate of sequelae is 33%.…”
Section: Discussionmentioning
confidence: 90%
“…Sun et al, in a retrospective review of 14 children with OMAS and neuroblastoma, reported that approximately 93% children had some neurological sequelae, with behavioral changes being the most common, followed by language impairments, motor retardation, and cognitive disorders. They also reported that the risk factors for neurological sequelae were the female sex, a residual tumor, and a non-adrenal-gland-located tumor [ 90 ]. Goh et al followed three children with OMAS from 4 to 10 years of age and reported that significant deficits in attention, processing speed, visuospatial skills, and language were observed in the long term [ 91 ].…”
Section: Reviewmentioning
confidence: 99%
“…10 Given the rarity of this disease, however, the limited research on the neurocognitive functioning of patients with NA-OMAS has been largely based on retrospective studies involving small samples and case reports. [11][12][13][14][15][16][17][18] There have been no prospective trials that included serial assessment of cognitive or psychological outcomes.…”
Section: Introductionmentioning
confidence: 99%